Exploring and proposing a positive change on engineering education and R&D strategic alignment to foster the economic growth in Colombia - DUARTE GARCIA, Jose andres (KDI School, 2015)
Some empirical studies suggest a relationship between economic growth and the number of engineers. In Colombia, the number of engineers has been part of discussions but through this work we suggest that the debate should be moved and focused on the quality of engineers since the quantity seems to be moving according the demand despite some arguments stressing the contrary. The quantity of engineers is important –and we will prove that the situation is not critical as has been stated during many years comparatively with other fields of knowledge- however it is more important for the current stage of development of Colombia to call the attention towards a fundamental aspect of the engineers being supplied: the quality and harmonization of them upon the economic growth. As will be explained in this work improving the quality of engineers is key to make the next generation of engineers more competitive and more aligned with the innovation and research needed in Colombia to bring better economic performance. Already the country aims the growth of some sectors that require a quality improvement on engineers able to apply reverse engineering and also do R&D which suffers from small number of researches, patents, projects aligned between public investment in R&D and market needs. Based on the endogenous growth theories, the number of engineers and good quality of them could develop R&D to improve the level of productivity and output understood as gross domestic product, GDP which is attached to the concept of economic growth and development. In this work we will go over the most relevant data and information referring to these issues and we will come with policy directions accepting that at this stage for Colombia the quality is more important than quantity and therefore government interventions with the support of the private sector and the academia is vital for boosting the economic development and future growth of Colombia. The Korean case of KAIST will be brought into consideration as a different alternative to push for the quality of engineers and more R&D to achieve better economic growth.
Thesis(Master) --KDI School:Master of Development Policy,2015